Postoperative dietary intake achievement: a secondary analysis of a randomized controlled trial - Ho, Chiou Yi; Ibrahim, Zuriati; Abu Zaid, Zalina; Mat Daud, Zulfitri Azuan; Mohd Yusop, Nor Baizura; Mohd Abas, Mohd Norazam; Omar, Jamil (MDPI, 2022)
Sufficient postoperative dietary intake is crucial for ensuring a better surgical outcome. This study aimed to investigate the postoperative dietary intake achievement and predictors of postoperative dietary intake among gynecologic cancer patients. A total of 118 participants were included in this secondary analysis. Postoperative dietary data was pooled and re-classified into early postoperative dietary intake achievement (EDIA) (daily energy intake (DEI) ≥ 75% from the estimated energy requirement (EER)) and delay dietary intake achievement (DDIA) (DEI < 75% EER) There was a significant difference in postoperative changes in weight (p = 0.002), muscle mass (p = 0.018), and handgrip strength (p = 0.010) between the groups. Postoperative daily energy and protein intake in the EDIA was significantly greater than DDIA from operation day to discharged (p = 0.000 and p = 0.036). Four significant independent postoperative dietary intake predictors were found: preoperative whey protein-infused carbohydrate loading (p = 0.000), postoperative nausea vomiting (p = 0.001), age (p = 0.010), and time to tolerate clear fluid (p = 0.016). The multilinear regression model significantly predicted postoperative dietary intake, F (4, 116) = 68.013, p = 0.000, adj. R2 = 0.698. With the four predictors’ recognition, the integration of a more specific and comprehensive dietitian-led supportive care with individualized nutrition intervention ought to be considered to promote functional recovery.